Patients' attitudes towards the potential use of stability tape to minimize head movements during cataract surgery. (18th August 2021) - Brogan, Kerr; Young, David; Ramaesh, Kanna; Lockington, David
ABSTRACT: Introduction: Head stabilization may reduce intra-operative risk during cataract surgery, but could be misinterpreted as "restraint." We wanted to establish patients' attitudes towards the potential use of stability-tape. Materials and Methods: One-hundred consecutive patients attending for local-anaesthetic cataract surgery were asked to complete a pre-operative questionnaire. This explored patient concerns and views regarding intra-operative head movement and the potential use of stability-tape. Results: All 100-patients completed the questionnaire. The median head movement concern score was 2 out of 10 (range 1–9, IQR 1–5). Eighty-four percent felt stability tape should be offered to all patients and 97% would consent for its' use. Only 6% voiced concern about the use of stability-tape (95% CI 2.2%, 12.6%). Conclusion: Patients had low concern for moving their head during surgery. The concept of stability-tape to minimize head movements during cataract surgery was viewed positively by most patients. This strategy may promote safer surgery in selected cases.